Peran Client Service dalam Business Development PT. Hashmicro Solusi Indonesia - Meiliea Meiliea; Muhammad Ghazi; Klemens Wedanaji Prasastyo; Nuno Sutrisno (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
This report is prepared as a brief explanation of the activities carried out during the implementation ot the MBKM (Merdeka Belajar Kampus Merdeka) Internship program at PT Hashmicro Solusi Indonesia. The Implementation of the Internship activities is carried out in the business development division, the client sub-division. Work in this division focuses on mining data for cold calls, entering leads data into the company’s system, collecting information related to client needs and offering the system needed by clients, confirming meeting schedules or presentation demos, and filling out daily report on business development, client service, and cold calls.